2005
DOI: 10.1177/107602960501100109
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function and Fibrinolytic Activity in Patients with Bronchial Asthma

Abstract: Platelets have the capacity to release mediators with potent inflammatory or anaphylactic properties. Platelet factor-4 (PF4) and beta-thromboglobulin (BTG) are two of these mediators. On the other hand, plasminogen activator inhibitor-1 (PAI-1) and tissue plasminogen activator (tPA) are two important mediators of fibrinolysis. Both mediators are secreted mainly by vascular endothelium. Plasma levels of PF4, BTG, PAI-1, and tPA may show changes in chronic inflammatory diseases such as asthma. This study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
2
30
1
3
Order By: Relevance
“…Similar observations were made in individuals having experienced an acute asthma attack [74] and in patients with nocturnal asthma [68]. In the latter study, the peak of platelet activation occurred concomitantly with the maximum increase in BHR, thus suggesting that platelets are partly responsible for the hyperresponsiveness or, at least, playing a role in the ensuing bronchoconstriction.…”
Section: Clinical Evidence For a Role Of Platelets In Asthmamentioning
confidence: 53%
“…Similar observations were made in individuals having experienced an acute asthma attack [74] and in patients with nocturnal asthma [68]. In the latter study, the peak of platelet activation occurred concomitantly with the maximum increase in BHR, thus suggesting that platelets are partly responsible for the hyperresponsiveness or, at least, playing a role in the ensuing bronchoconstriction.…”
Section: Clinical Evidence For a Role Of Platelets In Asthmamentioning
confidence: 53%
“…Indeed, the chronicity of platelet activation has been highlighted in studies where platelet activation has been shown to persist some time after the late asthmatic response has occurred in asthmatic patients [16], even though documented increases in platelet-leucocyte interactions within the circulation have returned to basal levels at 24 h post-allergen exposure [8], implicating platelets in chronic inflammatory events and airway remodelling [14,42]. Platelets may release a number of mitogens and enzymes that may contribute to airway remodelling directly, affecting bronchial smooth muscle growth, myofibroblast proliferation, subepithelial fibrosis, as well as altering the composition of the extracellular matrix after increased thrombopoiesis [42]. This response to injury is perhaps through the release of chemotactic factors for circulating structural cells [43].…”
Section: Platelets and Chronic Inflammationmentioning
confidence: 98%
“…31 Systemic increases in platelet activation are seen in patients with allergic asthma when challenged with allergen 32 and when experiencing an acute asthma exacerbation. 33 In women asthma has been shown to be associated with an increased prevalence of carotid atherosclerosis, 34 and recent data from the United Kingdom show that patients with asthma, as well as those with chronic obstructive pulmonary disease, have increased cardiovascular comorbidity. 31 Although cardiovascular complications in asthmatic patients have mostly been attributed to asthma treatment, 35,36 it cannot be excluded that systemic inflammatory mechanisms might make some contribution to the observed increase in risk.…”
Section: Systemic Consequences Outside the Respiratory Systemmentioning
confidence: 99%